Estudio cualitativo sobre los procesos de construcción de la identidad en campesinos de Nuevo Mundo, Zacatecas - Moya Vela, Jesús (SOCIAL REVIEW. International Social Sciences Review / Revista Internacional de Ciencias Sociales, 2017)
With grounded theory, categories and analysis codes were building and they have permitted on board how is it a group of rural populations, manifest their process of subjectivity how a result of the relations that this kind of economy promotes, and that are the interaction elements symbolic of their identity. The above marked in a context defined by the fact that the peasant production had been in decomposition. This work is part of a research that was used like a thesis project to towards the political science doctorate.